Investigating the discrepancy between MAIA and MP‐1 microperimetry results. (29th August 2021) - Xu, Lixing; Wu, Zhichao; Guymer, Robyn H; Anderson, Andrew J
Abstract: Purpose: Previous work has suggested that sensitivities measured on the iCare MAIA and Nidek MP‐1 microperimeters differ systematically, although it is unclear whether one or both devices are inaccurate. Here, we assess the discrepancy between these two instruments as well as with a rigorous reference standard. Methods: Fifteen healthy participants underwent visual field testing on the MAIA and MP‐1 microperimeters. Results were compared to a reference measure of increment thresholds on a laboratory‐based, calibrated computer monitor system using the same background luminance and target size. Discrepancies were assessed as a function of eccentricity along the vertical meridian. Differences in decibels (dB) due to differences in the maximum stimulus luminance between devices were accounted for mathematically. Results: The mean sensitivity measured with the MAIA was <1 dB lower than laboratory‐based measures, which was statistically significant but of limited clinical importance. In contrast, the mean sensitivity measured with the MP‐1 was >8 dB lower than the laboratory measures. The difference was greater for an eccentric superior retinal location, in contrast to what would be predicted if the discrepancy was due to a ceiling effect caused by the MP‐1's limited dynamic range. Conclusions: While MAIA measurements showed low bias compared with our rigorously determined reference standard, the MP‐1 showed large discrepancies that could not be explained purely by the limited dynamic range of the instrument. MAIA and MP‐1 sensitivity values cannot be compared directly, and caution is advised when assessing absolute sensitivities or eccentricity effects in the extensive MP‐1 literature.